2005
DOI: 10.1079/pns2005439
|View full text |Cite
|
Sign up to set email alerts
|

Should food or supplements be used in the community for the treatment of disease-related malnutrition?

Abstract: Strategies are needed for community-based treatment of disease-related malnutrition (DRM), which is a common debilitating condition that in the UK is estimated to cost > £7 · 10 9 annually. Whilst dietary fortification and counselling are often used as a first-line treatment for malnutrition, the numbers of dietitians available to undertake and oversee such practices are currently insufficient to address the extent of DRM in primary care. Although dietary fortification and counselling can improve nutritional (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 51 publications
(16 reference statements)
0
17
0
2
Order By: Relevance
“…Our results reveal that patients consuming oral nutritional supplements do not maintain their weight, and lost twice the weight of patients consuming regular foods. 35 This difference in our results may be related to relatively high BMIs among the majority of patients at baseline. 34 The meta-analysis revealed that the increases in body weight were mainly observed in patients with BMI <20 kg/m 2 .…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Our results reveal that patients consuming oral nutritional supplements do not maintain their weight, and lost twice the weight of patients consuming regular foods. 35 This difference in our results may be related to relatively high BMIs among the majority of patients at baseline. 34 The meta-analysis revealed that the increases in body weight were mainly observed in patients with BMI <20 kg/m 2 .…”
Section: Discussionmentioning
confidence: 58%
“…13 This recommendation aims to maintain adequate caloric and macronutrients and micronutrients, while minimizing weight loss. Similarly, a meta-analysis conducted by Stratton 35 concluded that oral nutritional supplements seem to be most effective in patients with a BMI <20 kg/m 2 (with 80% of the oral nutritional supplements energy being additive compared with 45% in those with a BMI >20 kg/m 2 ), or in patients who are malnourished at baseline. A metaanalysis by Paccagnella et al 34 evaluating the use of oral nutritional supplements in various cancer populations concluded that supplementation significantly increased total energy, protein, and micronutrient intakes, in addition to body weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These characteristics seem to be in contrast with indications of nutritional supplementation, mainly addressed to the compensation of micronutrient deficiencies due to an inadequate diet, lack of appetite, or concomitant diseases [28].…”
Section: Discussionmentioning
confidence: 96%
“…7 • Supplementation in community-based populations has shown mixed results. 8,9 • There is little evidence demonstrating dietitians can improve the problem. 10 The last fact is perhaps the most notable to the dietetic profession, but does this simply highlight the significant limitations when research is often driven by other professions?…”
Section: The Dietitians Role In Disease-related Malnutritionmentioning
confidence: 99%